Irish residential heating demand profile datasetMendeley Data - John Curtis; Niall Farrell (Data in Brief)
This data article describes the operation of gas and oil fuelled residential heating systems in Ireland. Based on almost 10,000 homes, the data presents information on the operation of domestic heating systems (whether turned on/off by the user), and the firing of the boiler during 2-hour slots across a period of two years ending in September 2021 by geographical region. The electrification of heating is government policy, with the ambition that hundreds of thousands of homes will switch from oil and gas fuelled residential heating to heat pumps. Such an outcome will have implications for electricity generation, transmission and distribution, especially during peak demand periods. This dataset can be used as a starting point to examine how additional residential heating loads will impact on the electricity grid and provide insight on where electricity grid strengthening works should be prioritised.